Affirmative Action untuk Demokrasi yang Berkeadilan Gender pada Pemilu 2009 - Valentina, Tengku Rika; Rusta, Andri (Jurnal Demokrasi, 2010)
Affirmative action is used as a basic for the quota of women in Central and Local Representative Body (Parliament). However, the quota itself is not the only way to struggle for gender justice. The Quota is arranged to facilitate women access in decision making to overcome the problem of a very complicated general election in Indonesia When the starting point of the women is long behind, the quota will be very important in order that competition and coordination run fairly. Kata Kunci: Â affirmative action, kuota, sistem pemilu, keadilan gender